Are supply shocks a key driver of global Inflation? Evidence from CPI and GDP deflator analysis - Noura Abu Asab (Research in Globalization, 2025)
This study investigates the main drivers of inflation measured by CPI inflation and GDP deflator across 20 advanced and emerging economies over the yearly span from 2014 to 2023. Using Principal Component Analysis and Panel Vector Autoregression, the research examines the roles of supply-side shocks, fiscal and monetary indicators, and trade openness. The findings indicate that supply-side factors, particularly food and oil price shocks as well as supply chain disruptions, are the primary contributors to both CPI and GDP deflator inflation. Fiscal and monetary factors exhibit limited short-term effect, while trade openness gains significance over time, especially for the GDP deflator, reflecting its broader economic impact. Variance decomposition reveals the persistent influence of supply-side factors, while trade openness plays an increasingly significant role in driving inflation in the long run. These findings provide a comprehensive understanding of inflation dynamics, emphasizing the need for tailored policy and cooperated interventions to mitigate external shocks, strengthen fiscal and monetary frameworks, and enhance global trade resilience.
Keywords: 330; Commodity Price; Cost-Push Inflation; Globalization; Inflation; Supply Chain Disruptions